2006
DOI: 10.1093/her/cyl148
|View full text |Cite
|
Sign up to set email alerts
|

Validating the theoretical structure of the Treatment Self-Regulation Questionnaire (TSRQ) across three different health behaviors

Abstract: Nearly 40% of mortality in the United States is linked to social and behavioral factors such as smoking, diet and sedentary lifestyle. Autonomous self-regulation of health-related behaviors is thus an important aspect of human behavior to assess. In 1997, the Behavior Change Consortium (BCC) was formed. Within the BCC, seven health behaviors, 18 theoretical models, five intervention settings and 26 mediating variables were studied across diverse populations. One of the measures included across settings and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
386
2
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 518 publications
(439 citation statements)
references
References 37 publications
19
386
2
8
Order By: Relevance
“…External and introjected regulation are classed as controlled forms of regulation, whereas identified, integrated, and intrinsic regulation are classed as autonomous forms of regulation. Various instruments have been developed to measure regulatory motives for exercise (e.g., Levesque et al, 2007;Li, 1999;Markland & Tobin, 2004). Studies in various populations have related these exercise regulatory motives to exercise participation (reviewed by Ingledew et al, 2009).…”
Section: Markland and Ingledew's (1997) Exercise Motivations Inventormentioning
confidence: 99%
“…External and introjected regulation are classed as controlled forms of regulation, whereas identified, integrated, and intrinsic regulation are classed as autonomous forms of regulation. Various instruments have been developed to measure regulatory motives for exercise (e.g., Levesque et al, 2007;Li, 1999;Markland & Tobin, 2004). Studies in various populations have related these exercise regulatory motives to exercise participation (reviewed by Ingledew et al, 2009).…”
Section: Markland and Ingledew's (1997) Exercise Motivations Inventormentioning
confidence: 99%
“…Internal consistency of each of the subscales is acceptable (most alpha values > 0.73). 27 The Perceived Competence Scale (PCS) (three versions: modified for fruit and vegetable, sodium intake, and exercise) consists of 4 items with a 7-point Likert response scale ranging from "not at all true" to "very true" and was designed to assess the degree to which an individual feels capable of changing his/her diet and exercise level. 26 A higher score on the PCS scale indicates more perceived competence.…”
Section: Methodsmentioning
confidence: 99%
“…The alpha reliability values for internal consistency of the PCS were acceptable at 0.89 for diet. 27 Although previous studies have shown the TSRQ and PCS to be valid and reliable in Caucasian and African-American populations, the model has not been specifically evaluated in a Mexican American population. Therefore, each of the seven measured SDT scales were evaluated for reliability and theoretical structure.…”
Section: Methodsmentioning
confidence: 99%
“…l self-determination theory constructs 20 -reported self-regulation of PA and dietary behaviours as measured by the Treatment Self-Regulation Questionnaire (TSRQ), 62 perceived autonomy in PA and dietary behaviours as measured by the Locus of Causality Scale (LCS), 63 perceived competence in PA and dietary behaviours as measured by the Perceived Competence Scale (PCS) 64 and perceived relatedness as measured by the Need for Relatedness Scale (NRS), 65 all as reported at 3.5 years l perceived satisfaction with current PA and dietary behaviours, 66 as reported at 3.5 years l self-reported use of behavioural techniques that are likely to be associated with long-term weight loss, including ongoing self-monitoring of weight/PA and the extent of establishment of dietary and PA daily routines, as reported at 3.5 years (see Q1a, Report Supplementary Material 2) l self-reported frequency of contact with other FFIT participants, coaches, football club-based initiatives and other health promotion/weight management initiatives since the end of the initial 12-week active phase of the FFIT programme, as reported at 3.5 years l self-reported major life events (e.g. bereavement, family illness, separation, divorce, redundancy) since the end of the initial 12-week active phase of the FFIT programme, as reported at 3.5 years l end-of-intervention weight change [from objective RCT baseline and 12-week measurements for the FFIT follow-up intervention (FFIT-FU-I) group and from self-reported (at 3.5 years) end-of-programme weight loss for the FFIT follow-up comparison (FFIT-FU-C) group] and pre-intervention weight change (from objective RCT baseline and 12-month measurements for the FFIT-FU-C group) l self-reported injury and joint pain, as reported at 12 months and at 3.5 years.…”
Section: Mediatorsmentioning
confidence: 99%